Understanding Financial Risk Management - Corelli, Angelo (Emerald Publishing Limited, 2024)
Financial risk management is a topic of primary importance in financial markets. It is important to learn how to measure and control risk, how to be primed for the opportunity of compensative return, and how to avoid useless exposure